Олімпізм в історії фізичної культури України - Anatolii Tsos; Nina Dedeluk (Lesya Ukrainka Volyn National University, 2022)
The Relevance of the Research. Ever since ancient times, Physical Education (PE) has been undergoing a process of formation, development, and enhancement in the territory occupied by modern Ukraine, and now it has become an integral part of ethnic culture. In current Research Papres, the historical aspects of PE and the contemporary applications of the physical culture traditions have been researched. However, the atmosphere of Olympism which has been present during the various historical periods of the physical culture development in Ukraine has never been the subject of specifically-focused study. Objective of the Research: To reveal the essence of Olympism in the history of PE in the territory of modern Ukraine. The Research Methods: analysis and generalization of scientific and ethnographic literature, induction and deduction, historical and logical methods, method of extrapolation. The Research Results. PE, in general, followed the tradition of ancient Greece and took place in gymnasia and palaestra, under the supervision of specially trained personnel. The program of the competition was quite broad and included pentathlon, pugilism, horseback riding, archery, swimming, dancing, and outdoor games, among others. Pentathlon consisted of wrestling, running, jumping, javelin throw, and discus throw. Extensive development of PE and sport in the Northern Seaside of the Black Sea led to close relationships with other sports policies in the Greek world. Athletes participated in the most prestigious competitions in Greece. Vicory was considered the highest achievement and brought fame and universal respect for fellow citizens. Conclusions. The tradition of Olympism in the history of PE in Ukraine reached the northern Black Sea area from the 7th century BC to the 2nd century AD. Over time, it created a unique PE system, based on national ideals of physical perfection, on the domestic and traditional ceremonies and customs of Olympism.